2021
DOI: 10.24853/mmj.2.2.62-69
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Medical Students’ Psychological in The Process of Distance Learning on Pandemic COVID-19

Abstract: Background: The spread of COVID-19 in Indonesia in June 2020 does not yet show signs of a decrease. Therefore, Indonesia's Ministry of Education and Culture takes preventive transmission in the educational environment by making the decision letter with four ministers agreeing that learning in higher education of the academic year 2020/2021 in all zones shall be held online. Online learning is a learning system that does not need face to face directly but uses a platform that can help the process of distance le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…1st year students most likely experience anxiety due to the lack of free time with family and entertainments with friends and tight schedule of classes and laboratory work on the 1st year curriculum. Meanwhile, 4th year students are burdened with thesis, OSCE (comprehensive final exam before proceeding into clinical clerkship at the academic hospital [19]. This is also in line with another study which found that junior students were more likely to be anxious than senior students [20].…”
Section: High Workload and Tight Schedulesupporting
confidence: 72%
See 1 more Smart Citation
“…1st year students most likely experience anxiety due to the lack of free time with family and entertainments with friends and tight schedule of classes and laboratory work on the 1st year curriculum. Meanwhile, 4th year students are burdened with thesis, OSCE (comprehensive final exam before proceeding into clinical clerkship at the academic hospital [19]. This is also in line with another study which found that junior students were more likely to be anxious than senior students [20].…”
Section: High Workload and Tight Schedulesupporting
confidence: 72%
“…Students who procrastinate can experience anxiety and stressful events, and due to low achievement as a result of procrastinating, they will likely suffer from depression [9]. Moreover, students might experience anxiety due to worrying about network interruptions during online lecture, especially as exam approaches [19]. The virus outbreak hinders students from completing numerous duties due to online learning.…”
Section: Studying At Home and Academic Procrastinationmentioning
confidence: 99%
“…( 9) Pada salah satu penelitian yang dilakukan oleh jun wang dkk, mengungkapkan hasil penelitian yang sebaliknya, bahwa mahasiswa tingkat awal mengalami stres yang lebih tinggi daripada tingkat akhir, hal ini pun selaras dengan penelitian yang dilakukan Gladys yang menyatakan bahwa tingkat stres mahasiswa tingkat pertama lebih tinggi daripada tingkat akhir. (10) Salah satu masalah akademik penyebab stres yang dialami mahasiswa FK adalah berlakunya kurikulum berbasis kompetensi, kurikulum ini menuntut mahasiswa untuk bergerak aktif. Penyebab lain yaitu pola komunikasi dosen dengan mahasiswa.…”
Section: Tingkat Pendidikanunclassified
“…Dampak negatif terhadap perilaku, berupa menunda-nunda penyelesaian tugas kuliah, malas kuliah, penyalahgunaan obat dan alkohol. (10) Gambar 1. Efek stres terhadap hipokampus, amigdala dan korteks prefrontal.…”
Section: Kesehatan Mentalunclassified
“…Based on research studies, the adaptation process faced by students and teachers is categorized into several factors, including psychological, physical, and economic obstacles (3,5). As a result of the spread of COVID-19, several psychologycal impacts have been experienced (4,6,7).…”
Section: Introductionmentioning
confidence: 99%